Administration safety of blood products: lessons learned from a national registry for transfusion and hemotherapy practice - Frietsch, Thomas; Schöler, Michael (Transfusion medicine and hemotherapy, 2017)
Background: Compared to blood component safety, the administration of blood may not be as safe as intended. The German Interdisciplinary Task Force for Clinical Hemotherapy (IAKH) specialized registry for administration errors of blood products was chosen for a detailed analysis of reports. Methods: Voluntarily submitted critical incident reports (n = 138) from 2009 to 2013 were analyzed. Results: Incidents occurred in the operation room (34.1%), in the ICU (25.2%), and in the peripheral ward (18.5%). Procedural steps with errors were administration to the patient (27.2%), indication and blood order (17.1%), patient identification (17.1%), and blood sample withdrawal and tube labeling (18.0%). Bedside testing (BST) of blood groups avoided errors in only 2.6%. Associated factors were routine work conditions (66%), communication error (36%), emergency case (26%), night or weekend team (39%), untrained personnel (19%). Recommendations addressed process and quality (n = 479) as well as structure quality (n = 314). In 189 instances, an IT solution would have helped to avoid the error. Conclusions: The administration process is prone to errors at the patient assessment for the need to transfuse and the application of blood products to patients. BST is only detecting a minority of handling errors. According to the expert recommendations for practice improvement, the potential to improve transfusion safety by a technical solution is considerable.
Gesehen am 04.04.2018